2015
DOI: 10.1590/1809-4430-eng.agric.v35n1p171-179/2015
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade na semeadura do milho

Abstract: RESUMO:O objetivo deste trabalho foi estabelecer um padrão para a qualidade na semeadura do milho. Durante cinco anos agrícolas, acompanhou-se a semeadura da cultura do milho em aproximadamente 13.500 ha, divididos em 30 propriedades da região dos Campos Gerais -PR, totalizando 64 semeadoras-adubadoras. Os parâmetros avaliados foram: variação da dosagem de adubo entre linhas, população inicial, variação de plantas emergidas entre fileiras, distribuição longitudinal, população final e produtividade. Conclui-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
7
0
7
Order By: Relevance
“…O valor obtido para distribuição normal (84,42%) foi abaixo da capacidade da semeadora pneumática, que deve ter como meta 90% de espaçamentos normais (TOURINO et al, 2009;MELO et al, 2013;WEIRICH NETO et al, 2015). A distribuição falha também não atingiu a meta para a distribuição longitudinal de sementes de 10%, apesar de obter valor pouco superior.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O valor obtido para distribuição normal (84,42%) foi abaixo da capacidade da semeadora pneumática, que deve ter como meta 90% de espaçamentos normais (TOURINO et al, 2009;MELO et al, 2013;WEIRICH NETO et al, 2015). A distribuição falha também não atingiu a meta para a distribuição longitudinal de sementes de 10%, apesar de obter valor pouco superior.…”
Section: Resultsunclassified
“…A semeadura do milho feita por semeadoraadubadora pneumática tem como meta de no mínimo 90% de espaçamentos normais na distribuição longitudinal de sementes (TOURINO et al, 2009;MELO et al, 2013;WEIRICH NETO et al, 2015). Porém, devido à elevada variabilidade de processos agrícolas esse resultado dificilmente ocorre, visto que o processo varia em função da matéria-prima, condições edafoclimáticas, sistemas mecanizados, índices de qualidade de operações agrícolas, qualificação de operadores, entre outros (ALBIEIRO et al, 2012) Neste contexto, tem-se aplicado o controle estatístico de processo (CEP) na agricultura com o intuito de identificar fatores críticos relacionados à eficiência e eficácia das operações agrícolas, por meio do controle efetivo de variáveis, limitandoas a padrões aceitáveis (NORONHA et al, 2011;MELO et al, 2013;VOLTARELLI et al, 2015).…”
Section: Introductionunclassified
“…Santos et al (2011) state that the increase in displacement speeds in seeding operation positively influences the number of failures row spacing during seeding. According to Weirich Neto et al (2015), the failures row spacing can be attributed to both the failure of the seeding mechanism and to the vigor and germination values of the seed itself, and the presence of the seeds was not verified in locations with failures row spacing.…”
Section: Resultsmentioning
confidence: 99%
“…Tourino et al (2007) reported that in the seed metering pneumatic the negative pressure can influence in the capturing of the seeds. To define the variation in the distribution of seeds (Table 2) as acceptable ˂ 10% or not ˃ 10% among the lines of the same seeder, the methodology proposed by Weirich Neto et al (2015) was adopted, calculating by the percentage among the number of seeds by lines, was obtained through the difference between the highest and lowest number of seeds divided by the lowest number of seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Schimandeiro et al (2006) also found variations among the sowing lines, with larger populations to the center lines. Weirich Neto et al (2015) evaluating 64 seeders in five crops, point out the variation over 10% among the lines of the same seeder, which could bring loss to the productivity. : not significant at 5% probability.…”
Section: Resultsmentioning
confidence: 99%